Efeito do treinamento suspenso na qualidade muscular de idosos - Medalha Junior, Ricardo Alessandro (Universidade Federal de São Carlos, 2023)
The aim of this study was to assess the effect of suspension training (ST) on muscle quality (MQ) in older adults. Twenty-two physically independent elderly men and women were recruited and assigned to ST or control groups (CON). The MQ of the upper limbs (UL) and lower limbs (LL) was established by a ratio between maximum dynamic strength and lean body mass, assessed through the 1RM test and dual-energy X-ray absorptiometry, respectively, before and after a 12-week intervention period. The significance level was set at P ≤ 0.05. The ST was able to promote increases in the strength of the UL and LL (P < 0.0001). However, only lean body mass of UL increased after 12 weeks of ST (P = 0.031) compared to CON. ST increased MQ for both QM of UL (P = 0.011) and MQ of LL (P < 0.0001), while the CON group did not show any significant changes (P > 0.05). These results indicate that ST can improve the MQ of older adults.
Effect of Suspension Training on Muscle Quality in Older Individuals
Keywords: Treinamento Físico; Envelhecimento; Qualidade Muscular; CIENCIAS DA SAUDE::EDUCACAO FISICA